2013
DOI: 10.1159/000353977
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of a Novel Prostaglandin Transporter, OAT-PG, Facilitates Renocortical PGE<sub>2</sub> Accumulation during Rat Pregnancy

Abstract: Background: Prostaglandin (PG)-specific organic anion transporter (OAT-PG) is a recently identified renal transporter involved in the local clearance of prostaglandin E2 (PGE2). Since the renal biosynthesis of PGE2 is not increased during pregnancy, this transporter expression would affect the gestational changes in the renal PGE2 content. Methods: Kidneys from rats at different gestational stages were used to examine gestational changes in the renocortical PGE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previously, Peti-Peterdi et al demonstrated in in vitro studies that the increased expression of cyclooxygenase-2 (COX-2) and the production of pros-taglandin E 2 (PGE 2 ) in macula densa cells stimulate renal renin synthesis from juxtaglomerular cells [2325]. Recently, we have further demonstrated in animal studies that the increase in renal PGE 2 was actually associated with the increase in local renin production [26]. Since thyroid hormone is known to positively regulate the renal expression of COX-2 and PGE 2 [27], this hormone was thought to stimulate renal renin synthesis by increasing the local production of COX-2 and PGE 2 in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Peti-Peterdi et al demonstrated in in vitro studies that the increased expression of cyclooxygenase-2 (COX-2) and the production of pros-taglandin E 2 (PGE 2 ) in macula densa cells stimulate renal renin synthesis from juxtaglomerular cells [2325]. Recently, we have further demonstrated in animal studies that the increase in renal PGE 2 was actually associated with the increase in local renin production [26]. Since thyroid hormone is known to positively regulate the renal expression of COX-2 and PGE 2 [27], this hormone was thought to stimulate renal renin synthesis by increasing the local production of COX-2 and PGE 2 in the kidney.…”
Section: Discussionmentioning
confidence: 99%